KEPENTINGAN INDONESIA DALAM EKSPOR KOPI KE MESIR TAHUN 2015-2019 - Andhika Rizaldi; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study analyzes Indonesia's interest in coffee exports to Egypt. The development of Indonesian coffee exports to Egypt in the period 2015-2019 has always been increasing in both export volume and value. Egypt is the largest destination for Indonesian coffee exports in the African region. The location of the country of Egypt, which is on one of the largest trade routes in the world, makes Egypt a very potential market for Indonesia in establishing trade cooperation. This is certainly very beneficial for Indonesia to gain trade interests. Several efforts and collaborations have been made between Indonesia and Egypt to continue increasing coffee exports to Egypt.          This research uses a qualitative method, with techniques of data collection through literature search drawn from various books, journals, articles, websites. This research uses the Mercantilism perspective and the international cooperation theory.          The results of this study indicate that Indonesia's political-economic interests in coffee exports to Egypt have three interests. First, by increasing coffee exports from 2015-2019, it can increase Indonesia's foreign exchange. Second, Indonesia penetrated the Indonesian coffee market in Egypt by controlling 60% of the coffee export market in Egypt. Third, Indonesia-Egyptian co-operation on coffee exports has made relations between the two countries stronger and more harmonious. Keywords: Export, Coffee, Interests, Indonesia, Egypt.